Rose Bengal-Mediated Photoinactivation of Multidrug Resistant Pseudomonas aeruginosa Is Enhanced in the Presence of Antimicrobial Peptides - Nakonieczna, Joanna; Wolnikowska, Katarzyna; Ogonowska, Patrycja; Neubauer, Damian; Bernat, Agnieszka; Kamysz, Wojciech (Frontiers in Microbiology, 2018)
Due to the overuse of antibiotics in medicine and food production, and their targeted mechanism action, an increasing rate in spreading of antibiotic resistance genes has been noticed. This results in inefficient therapy outcomes and higher mortality all over the world. Pseudomonas aeruginosa (carbapenem-resistant) is considered one of the top three critical species according to World Health Organization’s priority pathogens list. This means that new drugs and/or treatments are needed to tackle infections caused by this bacterium. In this context search for new/alternative approaches that would overcome resistance to classical antimicrobials is of prime importance. The use of antimicrobial photodynamic inactivation (aPDI) and antimicrobial peptides (AMPs) is an efficient strategy to treat localized infections caused by multidrug resistant P. aeruginosa. In this study, we have shown that the combined action of rose bengal (RB)-mediated aPDI together with cationic antimicrobial peptides (CAMEL or pexiganan) is efficient in inactivating the reference P. aeruginosa strain at concentrations lower than RB or AMP alone. Noteworthy, our treatment proved to be effective against all 35 clinical isolates of P. aeruginosa tested within this study, including these characterized as multiresistant. Moreover, we demonstrated that such treatment is safe and does not violate the growth dynamics of human keratinocytes.